2014
DOI: 10.1302/2046-3758.33.2000276
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular decorin influences the fibrosis genetic expression profile in a rabbit model of joint contracture

Abstract: ObjectivesThe goal of this study was to determine whether intra-articular administration of the potentially anti-fibrotic agent decorin influences the expression of genes involved in the fibrotic cascade, and ultimately leads to less contracture, in an animal model.MethodsA total of 18 rabbits underwent an operation on their right knees to form contractures. Six limbs in group 1 received four intra-articular injections of decorin; six limbs in group 2 received four intra-articular injections of bovine serum al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
(46 reference statements)
1
30
0
Order By: Relevance
“…The clinical relevance of the model we selected is well established and its core design has been adapted by a number of independent research groups. 2,7,[24][25][26][27][28][29][30][31][32] This model was employed as a part of an ongoing study that utilizes subcutaneous pumps to deliver compounds of interest to an injured rabbit. Here, we focused on the fibrotic processes in a group of untreated rabbits in which only phosphate buffered saline (PBS) was applied.…”
Section: Joint Contracture Modelmentioning
confidence: 99%
“…The clinical relevance of the model we selected is well established and its core design has been adapted by a number of independent research groups. 2,7,[24][25][26][27][28][29][30][31][32] This model was employed as a part of an ongoing study that utilizes subcutaneous pumps to deliver compounds of interest to an injured rabbit. Here, we focused on the fibrotic processes in a group of untreated rabbits in which only phosphate buffered saline (PBS) was applied.…”
Section: Joint Contracture Modelmentioning
confidence: 99%
“…Furthermore, microarray analysis of mRNA has demonstrated that the most notable changes in mRNA expression in capsular tissues occurred within the first 24 to 72 hours after injury. 13,14 Other studies have suggested the possible influence of mast cells on the development of arthrofibrosis in the four weeks after injury. 11 The early onset of changes, both on the cellular and molecular level, seems to indicate the need for early intervention to prevent or abort the development of arthrofibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…15 Decorin, while demonstrating change in the local mRNA expression, did not affect the overall degree of contracture. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The biologic prevention or treatment of arthrofibrosis may provide alternative therapies to improve ROM. Experimental approaches to limit the formation of fibrotic tissue in injured joints have included blocking the profibrotic activity of tissue growth factor β1 (TGF‐β1) with neutralizing antibodies or decorin, inhibiting vascular endothelial growth factor and fibroblast growth factor 2, and applying ketotifen to reduce profibrotic processes in mast cells that invade the injured joint tissues …”
mentioning
confidence: 99%
“…Experimental approaches to limit the formation of fibrotic tissue in injured joints have included blocking the profibrotic activity of tissue growth factor b1 (TGF-b1) with neutralizing antibodies or decorin, inhibiting vascular endothelial growth factor and fibroblast growth factor 2, and applying ketotifen to reduce profibrotic processes in mast cells that invade the injured joint tissues. [4][5][6][7][8][9] In this study, we tested the feasibility of limiting post-traumatic joint contracture by reducing the formation of collagen-rich deposits in the capsules of injured knee joints in rabbits. We aimed to directly interfere with the extracellular process of collagen fibril formation by blocking the critical collagencollagen interaction mediated by the C-terminal telopeptide region of collagen I molecules.…”
mentioning
confidence: 99%